Poor Prognostic Indicators of Scrub Typhus - Yadav, Shankar Prasad; Yadav, Sunil Kumar; Kanodia, Piush; Shah, Gauri Shankar; Bhattari, Narayan Raj; Uranw, Surendra (Journal of Nepal Paediatric Society, 2017)
Scrub typhus is an emerging disease in the eastern part of Nepal. Varied clinical presentation and lack of laboratory resources make diagnosis difficult. As this was the first known epidemic in this part of Nepal, unawareness resulted in late presentation with multiple complications and mortality. Hence this cases series alerts the clinician to be speculative for early diagnosis and management. J Nepal Paediatr Soc 2016;36(3):314-316